2006
DOI: 10.1002/dmrr.655
|View full text |Cite
|
Sign up to set email alerts
|

Densin and filtrin in the pancreas and in the kidney, targets for humoral autoimmunity in patients with type 1 diabetes

Abstract: Densin is a novel molecule shared by the kidney glomerular podocytes and pancreatic islet cells. Densin and filtrin can act as autoantigens, and autoantibodies against these can be detected in patients with type 1 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Consistent with its location at the slit diaphragm in renal podocytes, Densin is also found at adherens junctions of testicular Sertoli cells (Lassila et al. 2007) and was further identified in pancreatic islet cells (Rinta‐Valkama et al. 2007).…”
Section: Densin‐180 In Non‐neuronal Tissuementioning
confidence: 63%
“…Consistent with its location at the slit diaphragm in renal podocytes, Densin is also found at adherens junctions of testicular Sertoli cells (Lassila et al. 2007) and was further identified in pancreatic islet cells (Rinta‐Valkama et al. 2007).…”
Section: Densin‐180 In Non‐neuronal Tissuementioning
confidence: 63%
“…Recent studies have shown that over-expression of densin induces excessive neurite branching and outgrowth in cultured neurons: competitive binding of SHANK and dcatenin to the C-terminal domain appears to modulate this function (Quitsch et al 2005). Although densin was initially characterized as a brain-specific protein (Apperson et al 1996), recent studies have shown that densin is also expressed in the kidney and other peripheral tissues, where it is often localized to sites of cell-cell adhesion, suggesting key roles in modulating cell adhesion and cell-cell contacts (Ahola et al 2003;Heikkila et al 2007;Lassila et al 2007;Rinta-Valkama et al 2007).…”
mentioning
confidence: 99%
“…Apart from the important roles of nephrin/Kirrel proteins in specialized cellcell contacts and formation of the size-selective filter barrier in the kidney, nephrin has also been localized to the surface of insulin granules and the plasma membrane of the pancreatic ␤-cells, where it was proposed to function as an active component of insulin vesicle machinery that may affect vesicle-actin interactions and mobilization of insulin granules to the plasma membrane (29). Autoantibodies against Kirrel2 have been detected in patients with type 1 diabetes (30), raising the possibility that shedding of this membrane protein within the pancreatic islet, uptake by resident or circulating macrophages or dendritic cells, and antigen presentation in lymph nodes draining the pancreas are some of the mechanisms contributing to autoimmunity (31).…”
mentioning
confidence: 99%